Innovative approaches to developing national railway safety policy and training safety leaders (Транспортні системи і технології, 2024)
The article is aimed at considering innovative approaches in the formation of the national policy on safety in railway transport and on the training of safety leaders in this strategically important field. Focusing on today's challenges and opportunities, the article aims to identify key areas of development where innovation can improve safety and improve leadership training. It assesses the impact of technological and innovative changes on railway safety. The research also examines mechanisms and methods for introducing innovations into national railway safety policy, focusing on best practices from other countries and analysing the positive outcomes of such implementations. Additionally, it evaluates the competencies and skills required for leaders in the rail safety industry, highlighting key aspects of a leadership approach to solving security problems and developing national strategies. Furthermore, the study aims to develop training programs for security leaders by identifying essential elements and directions for training and creating innovative methods for skill development that address modern requirements and challenges in railway safety. This research provides a roadmap for enhancing railway safety through innovation and effective leadership, proposing actionable solutions and best practices to improve safety standards in the railway sector.